Introduction of waste charges and public resistance - Dunne, Louise (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
This paper reviews the potential for problems regarding public acceptability of environmental taxes. It examines the issue through a case study of the municipal waste charge protests in Ireland in 2003 and 2004. The example of these public protests against new waste charges demonstrate the necessity for good advertisement and PR when introducing a new tax. Rather than explain the polluter pays principle and simultaneously providing a good selection of options for recycling and composting, some municipalities moved straight into the new tax (for a service that had originally been free of charge and covered by general taxes). Outbreaks of public revolt occurred, with people blockading the streets and refusing to let the collection trucks down their road. Thus, even the people who had paid up were not getting their waste collected. The paper, which is part of ongoing work this area, seeks to identify the reasons why there was so much resistance to this charge and examine the lessons for the introduction of other environmental taxes and charges in the future. The literature on the various types of municipal waste charge is discussed with a view to seeing if pay-by-weight tends to be more politically acceptable as there is a real incentive and control over the amount of waste collected for landfill or incinerator.
Keywords: Urban geography -- Ireland